Why We Do That Thing We Do: What Consortia Executive Directors Want Library Directors to Know. Issue 1 (2nd January 2017) - Jones, Pamela
ABSTRACT: The consortium executive director is passionate about working with libraries and cultural organizations to connect similar and diverse institutions, enabling them to do things beyond their singular capability. Many library consortium executive directors worked in libraries before working at a consortium, but the job of the library consortium ED is in many ways different from that of a library director. A better understanding of these differences may help build stronger alliances between the consortium and its members. This article draws on the nonprofit leadership literature, library collaboration literature, and the responses to a brief survey of library consortia executive directors to explain the role and skills of the consortium executive director along with the challenges and opportunities for consortia.